A novel injection technique for ilioinguinal nerve block for post-operative pain relief in caesarean delivery - a randomized, double-blind, placebo-controlled trial - Khafagy, Wael; Elbassioune, Walaa; Ibrahim, Mohamed; Rady, Mahmoud; Abdeltawab, Ahmed; Altoraky, Muhammad; Hegazy, Mahmoud; Ayad, Waled; Alghazaly, Moatazza; Elshorbagy, Ahmed; Almorsy, Ahmed Shafik; Galal, Samir; et al. (Ceská gynekologie, 2023)
To determine whether the novel method is successful in blocking both ilioinguinal nerves to lessen postoperative pain following caesarean surgery. Between January 2022 and January 2023, 300 patients were enrolled in this study at the Obstetrics and Gynaecology Departments of the Faculty of Medicine at Al-Azhar University. About 150 of these patients received bupivacaine infiltration on both sides close to the anterior superior iliac spine, and 150 received a normal saline injection at the same locations. The study compared the two groups and discovered significant differences in the timing of analgesic requests, interval before the patient's first ambulation, length of hospital stay, postoperative pain score, and incidence of postoperative nausea and vomiting, with group A performing better. After a caesarean section, the local anaesthetic "bupivacaine" injection used to block the ilioinguinal nerves bilaterally is an efficient way to lessen postoperative discomfort and analgesic use.